Results of a Two-stage Technique for Treatment of Proximal Hypospadias with Severe Curvature: Creation of a Urethral Plate Using a Vascularized Preputial Island Flap - Ozcan, Rahsan; Emre, Senol; Kendigelen, Pinar; Elicevik, Mehmet; Emir, Haluk; Soylet, Yunus; Buyukunal, SN Cenk (Urology Journal, 2016)
Purpose: To present the results of a two-stage technique used for the treatment of proximal hypospadias with severe curvature. Materials and Methods: The medical records of children with proximal hypospadias and severe curvature were retrospectively analyzed. A 2-stage procedure was performed in 30 children. In the first stage, the release of chordee was performed, and a well-vascularized preputial island flap was created. The vascularized island flap was brought anteriorly and sutured over the ventral surface of the glans and degloved penile shaft. The second stage was performed 6-8 months later. A neourethra was reconstructed by the tubularization of the preputial-urethral plate utilizing the principles of Duplay technique. All surgical procedures were performed between 2005 and 2011. Results: The mean age of the patients was 4.4 years (1-17 years). The mean duration of urethral catheterization was 6 days after the first stage and 10 days following the second stage. The flaps were viable in all of the children. There was no residual chordee. Following the second stage (n = 30), complications developed in 11 children (36%), namely, a fistula in 7, a pinpoint fistula in 3, and a diverticulum formation in 1. The cosmetic outcome was satisfactory. Uroflowmetry measurements were evaluated, and only one patient had a diverticulum formation at the late follow-up. Conclusion: Vascularized preputial island flap is an alternative to free grafts for the reconstruction of the urethra. The main advantage of this flap technique is the creation of a thick, healthy and well-vascularized urethral plate. The advantages of this technique include better aesthetic appearance, an acceptable complication rate, and a very low rate of diverticula formation.